2013
DOI: 10.1103/physreve.88.022404
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of a horizontal phase boundary separating two miscible liquids

Abstract: The evolution of small disturbances to a horizontal interface separating two miscible liquids is examined. The aim is to investigate how the interfacial mass transfer affects development of the Rayleigh-Taylor instability and propagation and damping of the gravity-capillary waves. The phase-field approach is employed to model the evolution of a miscible multiphase system. Within this approach, the interface is represented as a transitional layer of small but nonzero thickness. The thermodynamics is defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…These results, including appearance of the cloudy regions near the droplet's ends, are is in agreement with the experimental pictures [22]. Figure 2 depicts the results of the numerical simulations of the droplet's time evolution obtained for the 4 In [37,38], the influence of the interface thickness on the stability of a phase boundary has been studied. It has been found that if the interface thickness is smaller than the thickness that corresponds to the thermodynamic equilibrium value δ 0 (21), then the thickness of the transition zone quickly adjusts to the thermodynamic equilibrium value, i.e.…”
Section: Numerical Resultssupporting
confidence: 73%
“…These results, including appearance of the cloudy regions near the droplet's ends, are is in agreement with the experimental pictures [22]. Figure 2 depicts the results of the numerical simulations of the droplet's time evolution obtained for the 4 In [37,38], the influence of the interface thickness on the stability of a phase boundary has been studied. It has been found that if the interface thickness is smaller than the thickness that corresponds to the thermodynamic equilibrium value δ 0 (21), then the thickness of the transition zone quickly adjusts to the thermodynamic equilibrium value, i.e.…”
Section: Numerical Resultssupporting
confidence: 73%
“…The linear stability of such an interface was studied in ref. [1], where it was shown that the interfacial diffusion slows down the development of hydrodynamic modes. From the other hand, in [1], it was also shown that thick interfaces, with the thicknesses exceeding the thickness of a thermodynamically equilibrium phase boundary, are prone to the new thermodynamic instability.…”
Section: Introductionmentioning
confidence: 99%
“…[1], where it was shown that the interfacial diffusion slows down the development of hydrodynamic modes. From the other hand, in [1], it was also shown that thick interfaces, with the thicknesses exceeding the thickness of a thermodynamically equilibrium phase boundary, are prone to the new thermodynamic instability. Thus, the thick interface would be thermodynamically unstable, and development of the instability would inevitably be accompanied by hydrodynamic motion, even if the lighter liquid lies over the heavier liquid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On macroscopic scales, the interface between two liquids is infinitely sharp, and the limit of δ → 0 is of the primary interest for the phase-field approach. As shown in [8], the limit of the sharp interface is not easy to obtain, as both the interface thickness and the surface tension coefficients depend on Ca, and both values would decrease if Ca tends to zero. Hence, a single decrease in the values of the capillary number would make the interface thinner, but a thinner interface would be also endowed with smaller surface tension.…”
Section: Governing Equations: Phase-field Approachmentioning
confidence: 99%